Digital instruments as invention machines - Koutroumpis, P; Leiponen, A; Thomas, LDW (Association for Computing Machinery, 2020)
An analysis of patenting history from 1850 to 2010 to detect long-term patterns of knowledge spillovers via prior-art citations of patented inventions.